REGULATION OF IBUPROFEN RELEASE RATE FROM MATRIX TABLETS - N. I. Filippova (Разработка и регистрация лекарственных средств, 2019)
Release profiles were investigated from tablets of ibuprofen in media simulating the conditions of the gastrointestinal tract. Carbopol Ultrez 21 was used as prolongator polymer. The formulations with three different neutralizing agents [L-lysine, N-methylglucosamine (MGA), sodium hydrocarbonate] in several carbopol : neutralizer ratios were tabletted with using the wet granulation method. Faster release of ibuprofen has been observed in formulations with sodium hydrocarbonate, than in formulations with amine containing L-lysine and MGA. Both the amount and neutralization rate of carbopol influence significantly on rate and extent of ibuprofen release from tablets. Carbopol swelling rate grows up with increasing of neutralizer content in tablet.